The Role of Cultural Changes in the Tendency to Childbearing Among Women - Samad Rasoulzadeh Aghdam; Fariba Pourjabbar Akhouni; Samad Adlipour (Gonabad University of Medical Sciences, 2020)
Background: Findings and published statistical data show that the fertility rate and the tendency towards childbearing are decreasing in many countries, including Iran. Many personal, social, economic, and cultural factors can cause this decline. Nonetheless, cultural changes have flourished, among other factors in recent years. Therefore, the study aimed to investigate the role of cultural changes in a childbearing tendency among women.  Methods: The research has a correlational design. The statistical population consisted of married women aged 15 to 45 years in Tabriz City, Iran, in 2017. The sample size was calculated as 384 with the Cochran formula. The samples were selected using a multistage cluster sampling method. The study measures were childbearing attitude scale, family values, religious values, global values, and a researcher-made individualism scale. The obtained data were analyzed using the Pearson correlation and multivariate regression.  Results: Findings showed that the tendency towards childbearing of women in Tabriz is low. Besides, there is a significant negative correlation between a tendency towards childbearing and variables of individualism (r=-0.37, P=0.000) and adherence to universal values (r=-0.35, P=0.001). But there is a significant positive relationship between the variables of adherence to family values (r=0.32, P=0.000) and religious values (r=-0.36, P=0.000) with the tendency towards childbearing. Additionally, independent variables introduced in the research regression model can explain 38% of the variations in the tendency towards childbearing.  Conclusion: The role of cultural factors affecting procreation should be considered to modify the current reducing trend of childbearing among Iranian families.